Exploring perinatal loneliness as a key social determinant of perinatal mental ill health in the UK: findings from a multidisciplinary consensus statement exercise that mapped knowledge about measurement, prevalence, antecedents, impacts and interventions, and agreed future priorities for research, policy and practice - Katherine Adlington; Rebecca Nowland; Lindsay Hunter; Katherine Hall; Suzanne Wilson; Naomi Finch; Nicola Wallis; Ruth Naughton-Doe; Jacqueline Kent-Marvick; Phoebe McKenna-Plumley; Emily Lovett; Thuy-Vy Nguyen; et al. (BMJ Open)
Objectives New parents are at increased risk of loneliness, which adversely affects parental and infant health and well-being and has been linked to an increased likelihood of parental mental illness. In the UK, perinatal mental illness is estimated to cost £8.1bn a year, predominantly due to lasting poor health and developmental consequences for children. The purpose of this consensus statement is to determine the state of this research field, highlighting key issues for researchers, policymakers and those responsible for perinatal mental health services and interventions. We will also highlight knowledge gaps to be addressed in future perinatal loneliness research.Design, setting and participants The Parental Loneliness Research Group held six online meetings between October 2023 and May 2024, attended by academics and practitioners from the UK and USA. Attendees conducted a mapping exercise by appraising published, unpublished and ongoing perinatal loneliness research. The findings were shared with advisory groups, including parents with lived experience of loneliness. A consensus statement was then drafted, reflecting existing knowledge and gaps in the current evidence about the experience of perinatal loneliness in the first 1001 days.Results A consensus about the definitions, measurement, prevalence, antecedents, impacts and interventions relevant to perinatal loneliness is outlined. Gaps in the literature are highlighted.Conclusions Despite emerging research into perinatal loneliness, it is hard to determine prevalence due to limited analyses of national survey data. Recommendations for future research include secondary data analysis; prioritising equality, diversity and inclusion; reconsidering solutions to perinatal loneliness through a social justice lens; co-producing interventions, and rigorous evaluation of existing interventions.